Gyzele Osmani interviewed by Ann-Mari Jordens - Osmani, Gyzele, 1970-; Jordens, Ann-Mari, 1940- (2006)
Gyzele Osmani, born 1970 in East Kosovo, Serbia, talks about her early life; the dispersal of Albanians and life in her village; the effect of the political situation on the education of Albanian Muslims by 1984; her marriage and her five children; a blockade of the village by the Serbian army (May 1999); leaving the village and walking towards Macedonia; conditions in the United Nations refugee camp; Macedonian Red Cross; the children becoming sick; her daughter's dislocated hip being diagnosed; meeting with Australian representatives but not understanding that Australia was only offering temporary protection; travelling to Australia with 400 other Albanians; the East Hills camp; contacting the doctors in Bandiana Safe Haven about her daughter's hip; the journey to Albury-Wodonga, the facilities there; her daughter's treatment in Wodonga hospital; being told on 3 March 2000 by the DIMIA that they had to leave Australia; Philip Ruddock's earlier visit to Bandiana (1999); Michelle Harris; pressure from the Dept. of Immigration to leave the Bandiana Safe Haven; Bandiana becoming a detention centre (2000), how it changed.
Osmani discusses the family's removal to Port Hedland, WA and the conditions in the camp; the system of numbering the refugees; getting to know the other refugees; the two mosques in the Centre; the playground equipment; schooling; the staff; the medical treatment available in Port Hedland; her family's health problems; keeping a diary (in Albanian); the isolation block in Port Hedland; psychiatric problems amongst the other refugees; how they got out of Port Hedland; how other Albanians from Presevo were repatriated; Michelle Harris; Marion Le; the people who helped her; John Molony and Janet Mathews from the Kingston Baptist Church; her depression; speaking out in the media; being told of their release following Ministerial intervention; arrival in Canberra; first impressions of Canberra; permanent residency; studying English; her daughter's hip and the need for a further operation; how her children have been affected by their time in detention; the Albanian community; her first job; studying Business Administration (2005); Melanie Poole; her story being published in a book by Eva Salis; speaking at a protest rally in Canberra against detention; SBS Insight Program (October 2001); the ABC Radio Eye program which won the 2003 Human Rights Radio Award; wanting to tell her story; her hopes for the future.
Recorded on May 7, 2006 at Red Hill, A.C.T.
Digital master available
Timed summary (7 p.) and uncorrected transcript (typescript, 105 leaves)
Keywords: Osmani, Gyzele, -- 1970- -- Interviews; Refugees -- Australian Capital Territory -- Interviews; Refugees -- Serbia -- Kosovo -- Interviews; Minorities -- Social aspects -- Australia; Detention of persons -- Australia; Aliens -- Institutional care -- Western Australia -- Port Hedland; Alien detention centers -- Western Australia -- Port Hedland